Mobile learning design and development to develop student decision making skills in social emotional learning process - Budi Astuti; Edi Purwanta; Rizqi Lestari; Caraka Putra Bhakti (Jurnal Konseling dan Pendidikan, 2021)
The development of technology and education is a set of two inseparable things. In education, technology affects both the learning process and the interaction between teacher and students. This condition poses a challenge for teachers, students, and schools to prepare innovative and exciting learning strategies so that the learning process runs optimally. This research aims to develop mobile learning as a learning medium in education. The research uses Research and Development Method with the ADDIE development model. The data collection method utilizes Social-Emotional in Learning Questionnaire previously tested for its validity and reliability to 30 students in Tangerang, Indonesia. The data analysis technique used is Pearson product-moment in quantitative approach. The results of this study reveal that there are 20 valid items of the SEL Questionnaire in addition to a model of mobile learning to equip decision making skill as one of the Social-Emotional skills needed in the 4.0 industrial revolutions. The model consists of 4 parts: pretest form, contents about decision-making skill, case study, and evaluation form. This research provides an alternative approach based on technology to enhance students' decision-making abilities in guidance and counselling services.